+0  
 
0
175
2
avatar

3m2 n-5 * m-2 n-3

Guest May 26, 2017
Sort: 

2+0 Answers

 #1
avatar+5553 
+2

\(3\cdot m^2\cdot n^{-5}\cdot m^{-2}\cdot n^{-3} \\~\\ =3\cdot m^2 \cdot m^{-2} \cdot n^{-5}\cdot n^{-3} \\~\\ =3\cdot m^{2+-2}\cdot n^{-5 + -3} \\~\\ =3\cdot m^0\cdot n^{-8} \\~\\ =3\cdot n^{-8}\)

hectictar  May 26, 2017
 #2
avatar+91231 
+3

And

 

\(3 \times n^{-8}\\ =3 \times \frac{1}{n^{+8}}\\ =\frac{3}{n^8}\)

Melody  May 26, 2017

26 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details